Effect of mediator on preparation of highly reactive electrogenerated zinc and its use in cross coupling reaction - Abdul Jalil, Aishah; Sundang, Murni; Triwahyono, Sugeng; Muhd. Muhid, Muhd. Nazlan; Kurono, Nobuhito; Tokuda, Masao (2005)
A new highly reactive zinc metal was readily prepared by electrolysis of a DMF solution containing polyaromatic compounds (PA) such as naphthalene and pyrene as a mediator and a supporting electrolyte in a one- compartment cell fitted with a platinum cathode and a zinc anode. This reactive zinc (EGZn/PA) was used for transformation of organic bromides into the corresponding organozinc bromides, which can not be achieved by the use of either reactive zinc (EGZn) or usual zinc metals. Reaction of the organozinc compounds thus prepared with various aryl iodides in the presence of 5 mol% of palladium catalyst gave the corresponding cross-coupling products in high yields.